Initial Experience With Ultra High‐Density Mapping of Human Right Atria. (23rd November 2015) - BOLLMANN, ANDREAS; HILBERT, SEBASTIAN; JOHN, SILKE; KOSIUK, JEDRZEJ; HINDRICKS, GERHARD
Ultra High‐Density Mapping of the Right Atria: Introduction: Recently, an automatic, high‐resolution mapping system has been presented to accurately and quickly identify right atrial geometry and activation patterns in animals, but human data are lacking. This study aims to assess the clinical feasibility and accuracy of high‐density electroanatomical mapping of various RA arrhythmias. Methods and Results: Electroanatomical maps of the RA (35 partial and 24 complete) were created in 23 patients using a novel mini‐basket catheter with 64 electrodes and automatic electrogram annotation. Median acquisition time was 6:43 minutes (0:39–23:05 minutes) with shorter times for partial (4.03 ± 4.13 minutes) than for complete maps (9.41 ± 4.92 minutes). During mapping 3, 236 (710–16, 306) data points were automatically annotated without manual correction. Maps obtained during sinus rhythm created geometry consistent with CT imaging and demonstrated activation originating at the middle to superior crista terminalis, while maps during CS pacing showed right atrial activation beginning at the infero‐septal region. Activation patterns were consistent with cavotricuspid isthmus‐dependent atrial flutter (n = 4), complex reentry tachycardia (n = 1), or ectopic atrial tachycardia (n = 2). His bundle and fractionated potentials in the slow pathway region were automatically detected in all patients. Ablation of the cavotricuspid isthmus (n = 9), the atrio‐ventricular node (n = 2), atrial ectopy (n = 2), and the slow pathway (n = 3) was successfully and safely performed. Conclusions: RA mapping with this automatic high‐density mapping system is fast, feasible, and safe. It is possible to reproducibly identify propagation of atrial activation during sinus rhythm, various tachycardias, and also complex reentrant arrhythmias.